Morphological and Biometrical Features of the Temporal Bone in Mongrel Dogs (Canis Lupus Familiaris) - Priya Pachauri; Archana Pathak; M.M. Farooqui; Shriprakash Singh; Anand Singh (Indian Journal of Veterinary Anatomy, 2026)
This study examined the anatomy of the temporal bone in Mongrel dogs (Canis lupus familiaris) based on morphological and biometrical analyses. The temporal bone, a paired structure, formed the ventro-lateral cranial wall and composed of squamous and petrous parts. The squamous part included a zygomatic process forming the zygomatic arch, while the petrous part housed ear components with petrous and tympanic subdivisions. Sexual dimorphism was evident, with males showing more prominent retroarticular process and wider zygomatic arches. Findings align with general canine anatomy and aid in diagnostics for ear conditions.